Vision Based Tracking and Interception of Moving Target by Mobile Robot Using Fuzzy Control - Mohamed Boumehraz; Zineb Habba; Rafia Hassani (Journal of Applied Engineering Science and Technology, 2018)
This paper presents a simple Fuzzy Logic Controllers (FLC) based control strategy to solvethe tracking and interception problem of a moving target by a mobile robot equipped with a pan-tilt camera. Before sending commands to the mobile robot, video acquisition and image processingtechniques are employed to estimate the target’s position in the image plane. The estimatecoordinates are used by a fuzzy logic controller to control the pan-tilt camera angles. The objectiveis to ensure that the moving target is always at the middle of the camera image plane. A secondFLC is used to control the robot orientation and to guarantee the tracking and interception of thetarget. The proposed pan-tilt camera and robot orientation controllers’ efficiency has beenvalidated by simulation under Matlab using Virtual Reality Toolbox.